2015
DOI: 10.1111/jmwh.12363
|View full text |Cite
|
Sign up to set email alerts
|

The Clinical Learning Dyad Model: An Innovation in Midwifery Education

Abstract: There is a national shortage of women's health and primary care providers in the United States, including certified nurse-midwives and certified midwives. This shortage is directly related to how many students can be trained within the existing system. The current model of midwifery clinical training is based on apprenticeship, with one-on-one interaction between a student and preceptor. Thus, the number of newly trained midwifery providers is limited by the number of available and willing preceptors. The clin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
1
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 21 publications
0
10
1
2
Order By: Relevance
“…Third, our findings did not always align with previous literature from other health professions 43‐50 . In these studies, dyad learning was often tested in the beginning of clinical rotations.…”
Section: Discussioncontrasting
confidence: 92%
“…Third, our findings did not always align with previous literature from other health professions 43‐50 . In these studies, dyad learning was often tested in the beginning of clinical rotations.…”
Section: Discussioncontrasting
confidence: 92%
“…Programme directors and administrators in Nursing and Medicine often battle with student clinical placements [61]. The large number of students enrolled in undergraduate nursing and medicine against the dwindling clinical placement opportunities drives programme directors to be creative in guaranteeing that their students attain professional competencies [7]. This creativity in student clinical placement may justify the increased volume of literature from Nursing and Medicine.…”
Section: Discussionmentioning
confidence: 99%
“…The purpose of the placement, the placement activity, the location of the placement -including the length of placement, students, supervision and placement facilitators -are identi ed as variables of a clinical placement model [6]. Clinical placement models that increase placement capacity, are cost-effective and ensure a positive learning culture, are critical for competence development [7]. Innovations in undergraduate health professions education programmes must integrate relevant clinical placement models.…”
Section: Health Organization (Who) In the Framework For Action On Inmentioning
confidence: 99%
“…Advantages of this type of peer learning exist for the educator, near-peer mentor, and mentee. For the educator, studies have identified either a reduced teaching burden (Cohen et al 2015;Stenberg et al 2020), or an enhanced ability for the educator to teach higher level competencies (Sevenhuysen et al 2015;Tawfik et al 2016). Other advantages include having the mentor complete the orientation for the mentee (Mills et al 2017).…”
Section: Practical Benefitsmentioning
confidence: 99%